Preparation of lactic acid bacteria compound starter cultures based on pasting properties and its improvement of glutinous rice flour and dough - Dengyu Wang; Linlin Liu; Bing Wang; Wenjian Xie; Yanguo Shi; Na Zhang; Hongchen Fan (Food Science and Human Wellness)
The effects of 5 lactic acid bacteria (LAB) fermentation on the pasting properties of glutinous rice flour were compared, and suitable fermentation strains were selected based on the changes of viscosity, setback value, and breakdown value to prepare LAB compound starter cultures. The results revealed that Latilactobacillus sakei HSD004 and Lacticaseibacillus rhamnosus HSD005 had apparent advantages in increasing the viscosity and reducing the setback and breakdown values of glutinous rice flour. In particular, the compound starter created using the two abovementioned LAB in the ratio of 3:1 had better performance than that using a single LAB in improving the pasting properties and increasing the water and oil absorption capacity of glutinous rice flour. Moreover, the gelatinization enthalpy of the fermented samples increased significantly. For frozen glutinous rice dough stored for 28 days, the viscoelasticity of frozen dough prepared by compound starter was better than that of control dough, and the freezable water content was lower than that of control dough. These results indicate that compound LAB fermentation is a promising technology in the glutinous rice-based food processing industry, which has significance for its application.